Streamlining Environmental Permits through Information Systems : Makassar's Experience - Delly Mustafa; Siti Zaleha Soebarini; Nurasia Natsir (International Forum of Researchers and Lecturers, 2025)
This study examines the effectiveness of Management Information Systems (MIS) in environmental permit administration within the Environmental Agency of Makassar City during the 2023-2024 period. Employing a qualitative case study approach, the research integrates several theoretical frameworks including Systems Theory, Technology Acceptance Model (TAM), Resource-Based View (RBV), Diffusion of Innovations, and Contingency Theory to comprehensively evaluate MIS performance. Through in-depth interviews with 35 respondents, direct observations, and documentation analysis over six months, the research identifies the impact of MIS implementation on environmental governance. Findings reveal significant improvements in processing efficiency (42% time reduction), administrative error reduction (67% decrease), and enhanced stakeholder engagement (53% increase in public participation). Nevertheless, challenges persist in regulatory alignment, technical reliability (12% system downtime), and user adaptation (23% of staff reporting usage difficulties). The study underscores the importance of continuous system optimization, targeted training, and cross-departmental integration for sustainable environmental governance. Theoretical contributions include an integrated MIS evaluation model for environmental administration contexts, while practical implications offer recommendations for technology-based permitting process improvements. Research limitations include a single geographic focus and relatively short observation period, suggesting the need for future longitudinal and comparative studies.